Índice de rendimento experimental ótimo de um gerador elétrico monofásico de uso ordinário - Lima, Kamilla Rayssa Lucas de (Universidade Federal Rural do Semi-Árido, 2019)
Nowadays the use of electricity is essential, being constantly used in industries, trades and also in the domestic part. This dependence of the general population on electricity is due to the fact that there are several facilities to use it. From this need we can identify the electric generator as an important machine to perform various activities, with the main purpose of electric power generation. The generators are much targeted, especially in times of energy crisis - which is responsible for the increased number of blackouts - and generate several losses for the country. Thus the idea of producing one's own energy becomes a means of circumventing such an event. ANEEL allows citizens / consumers to generate their own energy from renewable energy sources or not, and even be compensated if this energy is injected into the energy grid. The study about this theme is still able to provide us with information about the electric generator, such as the optimal point - maximum yield index. It is possible to obtain the efficiency index of a generator by varying the electrical charge through tests that include the generator and the workbench. The objective of this work was to achieve the best single-phase generator power generation rate through tests with variation of the generator's electric load. And it was through tests that it was found that the Toyama brand electric generator has better performance when operating with 78% of electric charging and when we consider better electric and economic performance this becomes the electric charging that generates greater autonomy. to the generator.
Monografia
Keywords: Gerador síncrono; Energia elétrica; Carregamento elétrico; Autonomia; ENGENHARIAS::ENGENHARIA MECANICA